Historical micronutrient psychiatry: descriptive analysis of patients with pellagra admitted to the "San Lazzaro" asylum in Reggio Emilia (Italy) in the decade 1901-1910: Pellagra in an asylum at the beginning of ‘900 - Pingani, Luca; Garagnani, Anna; Marchi, Mattia; Bombardieri, Chiara; Galeazzi, Gian Maria (Medicina Historica, 2022)
This study aims at describing the socio-demographic and clinical characteristics of the patients affected by pellagra and admitted to the “San Lazzaro” psychiatric asylum (Reggio Emilia, Italy) from 1901 to 1910 besides exploring possible gender differences for the collected information. Data were collected from the admission register and clinical records of those patients who were admitted to the San Lazzaro Psychiatric Hospital receiving a diagnosis of pellagra at their first admission. The pellagrous patient population was characterised by a higher rate of hospitalisation for women (64.3%) and the number of hospitalised patients suffering from pellagra gradually decreased from 1901 (78; 8.3%) to 1910 (8;0.7%). The most common profession for men admitted with pellagra was farmer/agricultural labourer, while most of the women were housewives. A characteristic shared by both the male and female population of inpatients was very high rate of illiteracy: only one patient was recorded as being able to read and write. The generic diagnosis of “mental illness from pellagra” was predominant (70%), while “dementia from pellagra” accounts for 17.85% of the admission diagnoses: no statistically significant differences between men and women were found in the frequency of diagnosis. Half of the patients, both men and women, died while being inpatients. This study confirms previous findings about the case mix of pellagra patients admitted to psychiatric hospital at the beginning of the last century in northern Italy and highlights the significance of the relationship of psychiatry with other medical disciplines and the sociocultural milieu.